Study on the Effect of the Obstacle on Heat Transfer Oxidation Spontaneous Combustion Characteristic of Coal Gangue Fracture. Issue 15 (18th November 2021) - Pan, Rongkun; Qiu, Tian; Zhang, Xuebo; Xiao, Zejun; Li, Cong; Ma, Hongyan; Wang, Jian
ABSTRACT: To address the coal gangue fracture heat transfer problem, the law of heat transfers and temperature distribution in the coal gangue fracture is studied. The temperature distribution in a coal gangue fracture under 12 conditions (with or without the obstacle, and various heat flows) is simulated via Fluent numerical simulation. The results show that the heat flow velocity, temperature and obstacle are important factors in inhibiting heat transfer oxidation spontaneous combustion in the coal gangue fracture. When the heat flow temperature is constant, the low-velocity heat flow causes a large temperature drops in the coal gangue fracture; when the heat flow velocity is constant, the high-temperature heat flow also produces a large temperature drops effect; when the obstacle is present and the heat flow produces vortex pass through the obstacle, increasing the energy loss in the coal gangue fracture, causing the temperature in the coal gangue fracture to drop rapidly, and reach the lowest in the position of the obstacle. Obstacles can effectively inhibit the heat transfer characteristics in the coal gangue fracture and reduce the risks of oxidation spontaneous combustion of gangue after grouting.